European Small Business Finance Outlook: December 2012 - Helmut Kraemer-Eis; Frank Lang; Salome Gvetadze (European Investment Fund (EIF), 2012)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity1, securitisation, microfinance). It is an update of the ESBFO May 2012. We start by discussing the general market environment, then look at the main aspects of equity finance and the SME Securitisation (SMESec) market. Finally, we briefly highlight important aspects of microfinance in Europe.
Keywords: 330